Additional Value and Business Efficiency of Various Processing Bananas Product in The Border Area of Sebatik Island - Fairuz Indana; Irham Irham; Jangkung Handoyo Mulyo (Agro Ekonomi, 2018)
People who are living in banana production centers such as Sebatik Island have the opportunity to develop the products. Therefore, the purpose of this research are: (1) to know the added value from banana processing business in the border area of Sebatik Island and (2) to know the relative efficiency level of each banana processing business in the border area of Sebatik Island. The method used in this research was the added value of Hayami method which is to know the added value and the Data Envelopment Analysis (DEA) method of CCR with input orientation which is to know the relative efficiency level of banana processing business. The study of the added value of various proceed banana in the border area of Sebatik Island showed that the banana processing commodities provided an average added value of  IDR 16,375.28 /kg. The relative efficiency analysis of 15 DMU of banana processing agroindustry showed that most of the banana processing agroindustry in the border area of Sebatik Island is not efficient yet. 40% of banana processing agroindustry is efficient and other 60% is inefficient. The average relative efficiency value of banana processing agroindustry is 0.737.